Review on effect of repetitive rework on dissimilar austenistic stainless steel pipes by using GMAW orbital welding - Nur Izan Syahriah , Hussein; M. N. , Ayof; Tan, Huay Kean (Trans Tech Publications, 2015)
Dissimilar metal welding is widely applied to meet the rquirement of transition in mechanical properties and/or difference in working conditions. For instance, even though AISI 304 and AISI 316L are both belong to austenitic stainless steels, but they are applied in different working environment. AISI 304 is used at high temperature applications, whereas AISI 316L is used at low temperature. Repair welding is able to return a part back to its normal service life if weld failure happened due to service deterioration or defects during fabrication stage. However, repetitive heat input due to repair welding will cause changes in welded structure and properties. In this article, the effect of repetitive repair welding of dissimilar austenitic stainless steel pipes to the microhardness, tensile strength, microstructure and quality of the weldment has been reviewed.